Character Education Orientation In Learning Reading Skills - Alfi Syahrin; Marwan Hamid; Usman M; Amru Bin As; Muhammad H (Universitas Muria Kudus, 2021)
The problems surrounding character or morals that occur today are much more numerous and more complex than the character problems that occurred in previous times. The problem of character is a matter of thought as well as a common concern because this country can be considered a character crisis. Almost all the time, the media is filled with news of increasing promiscuity, rampant rates of violence against children and adolescents, drugs, theft, and deprivation have become social problems that have not been resolved completely. Therefore, the main purpose of this paper is to reveal and explain the orientation of character education in learning reading skills with the philosophy of religion and Pancasila. In this discussion, the problems, relationships, and proper strategies for implementing character in education will be revealed.